Phytoremediation of Laundry Waste by Using Brassica juncea and Brassica rapa - Monica, Yesi; Hamdan, Abd Mujahid; Yahya, Husnawati; Shakira, Aisha; Shapira, Dhiya (Journal of Community Based Environmental Engineering and Management, 2023)
Laundry waste is typically discarded directly into the environment, resulting in environmental contamination. The purpose of this investigation is to determine the efficacy of mustard plants (Brassica juncea and Brassica rapa) in reducing COD, TSS, TDS, turbidity, phosphate levels, increasing DO, and neutralizing pH in laundry waste treated with the Deep Flow Technique (DFT) system. Twenty plants in each series were exposed to each of the two plant treatments for six days. The removal efficiency of Brassica juncea for COD parameters was 94.1%, TSS was 84.8%, TDS was 69.4%, turbidity was 92.5 %, phosphate was 95.0 %, the increase in DO was between 6.2 mg/L and 7.8 mg/L, and pH values were between 8.0 and 7.1. During the treatment of Brassica rapa, the results indicated a decrease in COD by 88.2%, TSS by 80.3%, TDS by 65.3%, turbidity by 91.9%, phosphate by 88.9%, an increase in DO between 6.0 mg/L and 7.6 mg/L, and pH values between 8.2 and 7.2. According to the presented data, the two mustard plants (Brassica juncea and Brassica rapa) are capable and effective at reducing the concentrations of pollutant parameters in laundry waste.